Synthesis Of Ultrafine Ba07 Sr0.3 TiO3 by Mechanically Activating Process. - Mohd Noor, Ahmad Fauzi (Universiti Sains Malaysia, 2007)
The project 'Synthesis of Ultrafine Ba0.7 Sr0.3 TiO3 by Mechanically Activating Process' was successfully completed early 2008. As reported in the technical report attached, the single phase BST was produced successfully at a relatively low temperature of 500oC, albeit the challenges encountered during the synthesis, one of which is the caking problem as well as melting of phase formed. The caking effect was due to the mechanical activation process, while the melting phase was a result of the low meting chemicals used.